Genotype First Approach as a Diagnostic Strategy for Precision Medicine in Moroccan Families with Nephronophthisis - Batta, Ourayna; Cherkaoui, Imane J.; Rahmuni, Yasmina; Amllal, Nada; Soulami, Kenza; Sefiani, Abdelaziz; Lyahyai, Jaber (Journal of Pediatric Genetics, 2024)
Nephronophthisis is a group of autosomal recessive kidney diseases characterized by chronic tubulointerstitial abnormalities leading to kidney failure. The incidence of nephronophthisis varies globally, and its genetic heterogeneity presents significant difficulties in diagnosis. Herein, we present a molecular diagnosis of four unrelated Moroccan families fulfilling the clinical criteria of nephronophthisis. As first diagnosis step, screening for a homozygous NPHP1 gene deletion, the most common mutation, was performed by using multiplex polymerase chain reaction. Additionally, clinical exome sequencing was carried out on patients in whom no NPHP1 deletion was identified. Three novel pathogenic variants in NPHP1, INVS, and NPHP4 genes were identified and confirmed by Sanger sequencing in the proband and other family members. These variants are absent from genetic databases of patients and controls of Moroccan origin. The bioinformatics analysis classified these variants as pathogenic. Our findings expand the genotypic spectrum of nephronophthisis and highlight the importance of genetic testing in patients from low- and middle-income countries to obtain a precise diagnosis of nephronophthisis. This helps facilitate an appropriate and personalized genetic counseling and improves clinical outcomes for patients with this condition.
Keywords: nephronophthisis; NPHP1; INVS; NPHP4; novel mutation; clinical exome sequencing